(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This report examines the structural transformation of Makkah Province’s economy, Saudi Arabia’s second-largest economic region, focusing on the role of the Hajj and Umrah sector in shaping its economic structure. It shows that the region depends heavily on this single sector — religious tourism accounts for roughly 60% of the Kingdom’s tourism revenues and 25-30% of Makkah’s private-sector revenue — but this over-reliance creates structural fragility marked by sharp seasonality and weak resilience to external shocks, as starkly revealed when the sector nearly collapsed during COVID-19. The report also analyzes labor-market indicators, noting a 9.15% Saudi unemployment rate in the region (above the national average), a significant income gap between Saudi and non-Saudi households, and heavy reliance on expatriate labor in tourism (74.4%). The analysis draws on Perroux’s growth-pole theory and Hirschman’s unbalanced-growth theory to explain the concentration of economic activity in Makkah and Jeddah. It reviews ongoing Vision 2030 policies and projects (Makkah Metro, Haramain Train, King Salman Gate project, and the Pilgrim Experience Program) aimed at diversifying the regional economy, and recommends accelerating the shift toward cultural tourism, strengthening Saudization, developing infrastructure, and pursuing balanced regional development.